Moroccan transition strategies towards free trade with the EU in 2010 - Henry Alan Raymond; Fuad Harraqi (European Regional Science Association (ERSA), 1998)
The general strategy is one of the liberalization of the economy and the government regulations that control it. Labor is exepected to be reallocated through free market mechanisms which encourage foreign investment. Concurrently a stratgey is being developed to supply the necessary human capital through a revaluationa and redirection of the educational system. Labor categories will experience significant shifts, but certain sectors may not shift adequately to meet demand. The analysis shows the misalignment of certain labor allocation strategies.There is a significant pent up demand in the country for European goods and services which will be substantially released with customs union. The challenge of the government is to develop globally competitive industries/companies which will find significant adavantage in free trade and be able to offset the increase in imports by a corresponding increase in exports. The government has identified some possible sectors for encouragement and assistance. A strategy for foreign investment in such sectors is being considered. Possible adjustments in strategy are outlined.
Keywords: 330